Heterozygous PGM3 Variants Are Associated With Idiopathic Focal Epilepsy With Incomplete Penetrance - Liu, Xiao-Rong; Bian, Wen-Jun; Wang, Jie; Ye, Ting-Ting; Li, Bing-Mei; Liu, De-Tian; Tang, Bin; Deng, Wei-Wen; Shi, Yi-Wu; Su, Tao; Yi, Yong-Hong; Liao, Wei-Ping (Frontiers in Genetics, 2020)
Introduction Idiopathic focal epilepsy (IFE) is a group of self-limited epilepsy. The etiology for the majority of the patients with IFE remains elusive. We thus screened disease-causing variants in the patients with IFE. Methods Whole-exome sequencing was performed in a cohort of 323 patients with IFE. Protein modeling was performed to predict the effects of missense variants. The genotype-phenotype correlation of the newly defined causative gene was analyzed. Results Four novel heterozygous variants in PGM3, including two de novo variants, were identified in four unrelated individuals with IFE. The variants included one truncating variant (c.1432C>T/p.Q478X) and three missense variants (c.478C>T/p.P160S, c.1239C>G/p.N413K, and c.1659T>A/p.N553K), which were no allele frequency in gnomAD database. The missense variants were predicted to be damaging and affect hydrogen bonds with surrounding amino acids. Mutations Q478X, P160S, and N413K were associated with benign childhood epilepsy with centrotemporal EEG spikes. P160S and N413K were located in the inner side of the enzyme active center. Mutation N553K was associated with benign occipital epilepsy with incomplete penetrance, located in the C-terminal of Domain 4. Further analysis demonstrated that previously reported biallelic PGM3 mutations were associated with severe immunodeficiency and/or congenital disorder of glycosylation, commonly accompanying by neurodevelopmental abnormalities, while monoallelic mutations were associated with milder symptoms like IFE. Conclusion The genetic and molecular evidence from the present study implies that the PGM3 variants identified in IFE patients lead to defects of PGM3 gene, suggesting that PGM3 gene is potentially associated with epilepsy. The genotype-phenotype relationship of PGM3 mutations suggested a quantitative correlation between genetic impairment and phenotypic severity, which helps explain the mild symptoms and incomplete penetrance in individuals with IFE.